Utilization Of Prawn Shell Powder For The Production Of Chitinase By Kurthia Gibsonii Mb126 - MINI K PAUL; MINI K D; ALLY C ANTONY; DR.E K RADHAKRISHNAN; DR. JYOTHIS MATHEW (International Journal of Pharma and Bio Sciences, 2012)
239 bacterial isolates producing extracellular chitinase were selected from coastal environments of Kochi using a solid medium containing prawn shell powder. Among them 23 isolates which produced clear zone with diameter >1.5cm were tested for production of chitinase in a medium containing prawn shell powder. The bacterium designated as Mb 126 was the highest yielding and was selected for further studies. It was identified as Kurthia gibsonii. 0.6% of prawn shell powder, pH 6.5, temperature of incubation 350 C and agitation rate 100 rpm were the conditions optimum for chitinase production. This is the first report of chitinase production by kurthia gibsonii.